1987
DOI: 10.1136/bjsm.21.2.14
|View full text |Cite
|
Sign up to set email alerts
|

High intensity training and treadmill sprint performance.

Abstract: Twelve county standard hockey players completed a 30 second sprint on a non-motorised treadmill and an uphill treadmill running test to determine maximum oxygen uptake (VO2 max) before and after 6 weeks of high intensity training (fast runs 3-5 miles, intervals 30-300m and circuit training), whilst 11 club standard players completed the same tests without any additional training. For the county standard group there was an 11.1% and 5.0% improvement in peak running speed and distance covered on the sprint tread… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Four weeks of high intensity sprint interval training combined with endurance training increased motor units activation. Cheetham and Williams (1987) [6] found that 11.1% of improvement in peak running speed following high intensity training. Relatively brief period of sprint training increased anaerobic capacities in initially untrained individuals [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…Four weeks of high intensity sprint interval training combined with endurance training increased motor units activation. Cheetham and Williams (1987) [6] found that 11.1% of improvement in peak running speed following high intensity training. Relatively brief period of sprint training increased anaerobic capacities in initially untrained individuals [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…10,43 Aerobic Power According to Bangso 44,45 the development of VO 2 max is important in the recovery between high-intensity bouts. Research suggests that this is best achieved by interval training [46][47][48] as more work can be performed at higher intensities with the same or less fatigue compared to continuous training. By increasing a dancer's VO 2 max it allows them to carry out the same exercise at a lower relative workload thereby delaying the effect of fatigue, which is a major perceived cause of injury within dance.…”
Section: Aerobic Foundationmentioning
confidence: 99%